Academic Staff Practices and Challenges of Publishing:: Evidence from an Ethiopian University - Alehegn, Abatihun; Diale, Boitumelo Molebogeng (International Journal of African Higher Education, 2021)
This article reports on the findings of a study undertaken to establish practices and challenges to academic publishing at a higher education institution in Ethiopia. A descriptive survey design was employed and con- -venience and purposive sampling were used to select the sample. The data were gathered by means of a questionnaire with closed- and open-ended questions and were analysed using descriptive and thematic analysis. The results show that, despite the benefits of publishing, not all academics in the university are publishing in local and international journals due to a number of challenges. These include a lack of commitment and motivation, lack of experience and exposure to publishing, and inadequate information, knowledge and skills to access accredited journals. Academics also suffer from work overload, a lack of support from the university to publish, and challenges emanating from journals themselves. It is recommended that the university, the Ethiopian Ministry of Science and Higher Education and other relevant stakeholders should collaborate to address this situation. Key words: academics, academic publishing, higher education institution, challenges, practices, university